Baía de Castelhanos: o status de reserva extrativista e sua influência na proteção das comunidades tradicionais e do ecossistema - Massa, Ana Luiza Crozara (Universidade Federal de São Carlos, 2025)
The Castelhanos Extractive Reserve (RESEX), located on the northern coast of the State of São Paulo, in Ilhabela, has faced uncertainty since August 2022 regarding the potential loss of its legal status. This situation resulted from Law No. 1.546/2022, which extinguished the Reserve without considering public opinion or conducting a technical study. In response, the São Paulo Court of Justice suspended the revocation and granted an injunction declaring the act unconstitutional. Nevertheless, as the legal dispute remains unresolved, the traditional community of Castelhanos continues to live under uncertainty about the future of its territory. In this context, the present study aimed to analyze the perceptions of local fishers and other community members regarding the importance of maintaining the RESEX, investigating their historical relationship with the environment and how ecosystem preservation is intrinsically linked to cultural protection and the continuity of traditional practices. To achieve this, an ethnographic approach was adopted, supported by fieldwork, field diaries, semi-structured interviews, social cartography, and the construction of a seasonal fishing calendar, thereby integrating local and scientific knowledge. The findings demonstrate that the community perceives the RESEX not only as an instrument of environmental protection but also as a mechanism for strengthening cultural identity, social cohesion, and economic sustainability, underscoring the inseparable relationship between culture, territory, conservation, and belonging. The study also revealed external pressures such as real estate speculation, the expansion of large-scale tourism enterprises, and the impacts of climate change, which pose direct threats to both the preservation of the Bay and the community’s way of life. Testimonies emphasized feelings of belonging, tranquility, and security within the territory, while also denouncing legal uncertainties and the challenges of enforcement, which often favor predatory activities such as illegal industrial fishing. It is concluded that the environmental preservation of the Castelhanos Bay can only be fully understood when articulated with the appreciation of traditional ways of life, which ensure both the conservation of natural resources and the cultural and social reproduction of the community. This research contributes to strengthening the struggle for territorial rights, bringing greater visibility to traditional populations, and highlighting the importance of Extractive Reserves as public policies that combine environmental conservation with social justice. The results are expected to provide support for the development of more effective participatory management strategies, as well as encourage further studies on the impacts of real estate speculation and climate change in the region.
Castelhanos Bay: the extractive reserve status and its influence on the protection of traditional communities and the ecosystem
Keywords: Etnografia; Pescadores; SNUC; Ethnographic; Fisherman; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA RURAL; 2. Fome Zero e Agricultura Sustentável